Osnove za konstrukcijo algoritmov minimalne porabe goriva pri vleki - Lenart, Ladislav (Strojniški vestnik, 1999)
The design of algorithms for solving some low level problems in time table planning for Slovenian railways is described. The main aims is the use of the minimum amount of fuel. The algorithms are based on a solution of a variational problem with extensions to various types of boundary conditions. The use of the Hamiltonian theory has been avoided and the solutions are based on more simple derivations.
Keywords: Slovenske železnice; načrtovanje voznih redov; algoritmi; poraba goriva; matematični modeli; železnice